A Survey of Containner Breeding Mosquito Species in Kuching Area - Yeo, G.G; Vimalanathan, S.; Lee, L.K; Balakrishnan, A. (Universiti Malaysia Sarawak (UNIMAS), 2011)
A visual larval inspection was done from October 2010 to January 2011 to identify the common species of container-breeding mosquitoes in Kuching, Sarawak. A total of 14 areas in Kuching were surveyed. All the 1216 larvae collected were identified. The dominant species was Ae. albopictus (79.03%), followed by Culex sp. (20.97%). The most common breeding sources were plastic containers. The container index was the highest for Taman Budaya, Kuching (83.33%). Larval breeding habitats were found within the temperature range of 25.1⁰C to 33.0⁰C and pH of 3.0 to 9.9. There is no significant difference of water temperature between Ae. albopictus (30.2⁰C ± 1.0) and Culex sp. (30.2⁰C ± 0.6). However, the pH of water for Culex sp. (7.6 ± 0.1) was found significantly lower than that of Ae. albopictus (7.8 ± 0.9). Mean pH of natural containers (6.7 ±1.3) was significantly lower than mean pH for artificial containers (7.8 ± 1.1). Mix breeding of Ae. albopictus and Culex sp. was found in coconut and plant saucers collected from Kampung Kudei and Waterfront, respectively. Based on its dominance and versatility, we suggest that Ae. albopictus may present as a sole vector for dengue virus in Kuching.